ANALISIS PENERAPAN APLIKASI SISTEM KEUANGAN DESA MARO SEBO, JAMBI LUAR KOTA, MUARO JAMBI - Makhshushi Zakiyah; Yessi Mauliyah; Ahmad Hamdi (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
Since the reform era, the village government has the authority and independence to carry out village development in accordance with the needs of the community. So that the development gap between regions and poverty can be minimized. However, this needs to be supported by a system that can support the application of the principles of transparency and accountability in financial management. The presence of the Village Financial System (Siskeudes) application used by the Maro Sebo village government since 2017, has supported village fund financial management activities in accordance with Permendagri Number 20 of 2018. Starting from planning, implementation, administration, reporting, and accountability. The financial reporting process becomes faster, on time, more accountable